2008
DOI: 10.1074/jbc.m803511200
|View full text |Cite
|
Sign up to set email alerts
|

The Protonation State of the Cross-linked Tyrosine during the Catalytic Cycle of Cytochrome c Oxidase

Abstract: The deprotonated Tyr-280 must be reprotonated later on in the catalytic cycle to serve as a proton donor for the next oxygen reduction event. To find the reaction step at which the crosslinked Tyr-280 becomes reprotonated, all further steps of the catalytic cycle after O-O bond cleavage were followed by infrared spectroscopy. We found that complete reprotonation of the tyrosine is linked to the formation of the one-electron reduced state coupled to reduction of the Cu B site.Cytochrome c oxidase (CcO) 3 contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
70
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 46 publications
18
70
0
Order By: Relevance
“…However, even if there may be an error in the calculations with regard to the order of the O B and the O H states, the O B state will not be significantly lower than the O H state, and the copper reduction potential would still be high in the O B state. It can also be noted that the small energy difference between the O H and O B states, is in line with the observation that the tyrosine residue becomes partially reprotonated in the oxidized intermediate at acidic conditions [24].…”
Section: Magnetic Coupling Between Cu(ii) and Fe(iii)supporting
confidence: 54%
“…However, even if there may be an error in the calculations with regard to the order of the O B and the O H states, the O B state will not be significantly lower than the O H state, and the copper reduction potential would still be high in the O B state. It can also be noted that the small energy difference between the O H and O B states, is in line with the observation that the tyrosine residue becomes partially reprotonated in the oxidized intermediate at acidic conditions [24].…”
Section: Magnetic Coupling Between Cu(ii) and Fe(iii)supporting
confidence: 54%
“…The remaining two chemical protons are transferred via the K pathway. A likely factor for this duality is the special role of Tyr-244 at the end of the K pathway, a residue implicated in the chemistry of dioxygen bond-breaking as a proton and electron donor (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…FTIR data (21) suggested that the cross-linked tyrosine is a deprotonated tyrosinate in both the F and O states. The proton taken up into the BNC upon reduction of state F is thus likely to form a ferric heme a 3 hydroxide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The crosslinked tyrosine is unprotonated (21) so that the cupric Cu B will have either a water molecule as the fourth ligand or no fourth ligand at all. The reason for this is that the oxidation of the fully reduced enzyme is coupled to net uptake of no more than two protons, which occurs in the steps P→F and F→O (Fig.…”
Section: Rationalementioning
confidence: 99%